FAKTOR PENGHAMBAT KONSEP GREEN PORT DI PT TERMINAL TELUK LAMONG PELABUHAN SURABAYA - Duyesna Perawati; Putri Aksa Nabila; Dedeng Wahyu Edi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The purpose of this research is to find out the obstruction factors of green port concept at PT. Terminal Teluk Lamong in Surabaya Port. The method of the research used Fishbone Diagram to seek the main problems using 5 why keys. The result shows that the obstruction factors are the power plant, gas fuel of bulk cars, ships service, charging stations of gas fuel, clear water management, sterile dock area, and the discipline of the employees. The solution needed to be done as soon as possible is the on-time development.